The Historical Metaphor Meaning of “The Secret History of the Mongols” - Dugerjav, Badamdorj (Mongolian Language and Literature Studies, 2024)
The author observed metaphors of the Secret History of the Mongols in detail in his academic article, and explained how Mongolians abstractly thought and developed metaphorical way of thinking more than 780 years ago. In particular, he pointed out that there many metaphors used to describe some characteristics of Mongolian people, by recognizing the behavior of animals, fish, and birds. For example, in the Section 78 of the Secret History of the Mongols, When Temüjin and Khasar came to the house, ... Öelün Üjin reprimanded using harsh, and old wordings such as “… Noqay metü, qablan metü, arslan metü, mangγus metü, singqor metü, čuraqa metü, buura metü, čino metü, anggir metü, čöeböri metü, bars metü, baruq metü.” (Secret History of the Mongols, 1985:30). Also, the author explained the lexemes with transferred meanings such as God, golden, dog, etc., as well as metaphorical words as like/as, so much/that much, and turn to after comparing mythological and pagan idol names of the Secret History of the Mongols with human and animal names. He concluded that some proper names and collocations such as Börte Činо, Goo Maral, Chinggis, a reddish cow, a red bull, a pale yellow man, like an yellow dog, Teb Tenggeri have historical metaphor meanings. It can be considered that metaphors of the Secret History of the Mongols may be divided into two categories such as 1. Language metaphor and 2. Literary metaphor. “Монголын Нууц Товчоон”-ы түүхэн метафорын утга Хураангуй: Зохиогч эл эрдэм шинжилгээний өгүүлэлдээ: “Монголын Нууц Товчоон”-ы метафорыг нарийвчлан ажиглаж, 780 гаруй жилийн тэртээ монголчууд хийсвэрлэн сэтгэж, метафор сэтгэлгээ хөгжиж байсныг тодолжээ. Ялангуяа, амьтан, загас, шувууны аяг араншныг танин мэдээд, монгол хүний зарим зан чанарыг зүйрлэн илэрхийлсэн түүхэн метафор элбэг байгааг онцлон дурджээ. Тухайлбал: “Монголын Нууц Товчоон”-ы 78 дугаар зүйлд: Тэмүжин Хасар хоёр гэрт ирж ороход, ...Өэлүн үжин: “... Noqay metü, qablan metü, ar slan metü, mangγus metü, singqor metü, čuraqa metü, buura metü, čino metü, anggir metü, čöeböri metü, bars metü, baruq metü.” (МНТ, 1985:30) гэх зэргээр хуучин үгс үндэслэж, өтгөс үгс эшилж, машид зэмлэсэн ажээ. Мөн зохиогч түүхэн метафорыг илэрхийлж буй, утга шилжүүлсэн бурхан, алтан, нохой гэх зэрэг үглэвэр, метафорын илтгэгч мэт, төдий, бол- гэх мэт үглэврийн утга учрыг тайлбарласан бөгөөд тус өгүүлэлдээ зохиогч “Монголын Нууц Товчоон”-ы домог зүйн болон онгон шүтээний зарим нэрсийг хүн, амьтны нэртэй харьцуулж үзээд, Бөртэ Чоно, Гоо Марал, Чингис, Ухаагч үнээ, Улаан бух, Цэгээн шар хүн, Шар нохой мэт, Тэв Тэнгэр гэх мэт оноосон нэрс, нийлэмж үгс бол түүхэн метафор утгатай гэж үзжээ. “МНТ”-ы метафорыг 1. Хэлний метафор, 2. Уран зохиолын метафор гэж хоёр ангилжээ. Түлхүүр үг: Монголын нууц товчоон, утга зүй, түүхэн метафорын утга